A Novel Filtering Algorithm of Data Acquisition for Electrical Capacitance Tomography - YANG Ting; CHEN De-yun; WANG Li-li (Journal of Harbin University of Science and Technology)
On the basis of analyzing the filtering algorithm of ECT data acquisition system，according to the characteristics of Kalman filter and wavelet transform，a filtering algorithm based on the characteristics of Kalman filtering and wavelet transform is proposed about the acquisition accuracy and real-time requirement of electrical capacitance tomography ECT ( Electrical Capacitance Tomography) data acquisition system. This algorithm first makes signal acquired data processed by multi wavelet to obtain stable observed data，then estimates the noise statistics by noise statistical estimator to ensure the stability and convergence of the signal． Finally，cexe get the signal more accurately by Kalman filtering. The simulation experiment results show that the proposed algorithm has better denoising effect compared with the Kalman filter algorithm which can obtain the signal more precisely and reliably and improve the data acquisition precision of ECT data acquisition system． It provides a novel filtering method for ECT data acquisition system.